Epigenetics in the Brain: A Study in a Rat Model of Neuropathic Pain - Diogo Rafael Rodrigues (2021)
The role of epigenetics in chronic pain at the supraspinal level is yet to be fully characterised. DNA histone methylation is crucially regulated by de novo methyltransferases (DNMT1-3) and ten-eleven translocation dioxygenases (TET1-3). Evidence has shown that 5mC markers are altered in different CNS regions related to nociception, namely the dorsal root ganglia, spinal cord, and diverse brain areas. Decreased global methylation was found in the DRG, prefrontal cortex and amygdala, associated with decreased DNMT1/3a expression; and increased 5hmC levels as well as mRNA levels of TET1 and TET3 were found linked to augmented pain hypersensitivity and allodynia in inflammatory and neuropathic pain models. Since epigenetic mechanisms may be responsible for the regulation and coordination of various transcriptional modifications described in chronic pain states, with this study, we aimed to evaluate the functional role of TET1-3 and DNMT1/3a genes in neuropathic pain in several brain areas. In a spared nerve injury rat model of neuropathic pain, 21 days after surgery, we found increased TET1 expression in the medial prefrontal cortex and decreased expression in the caudate-putamen and amygdala; TET2 was upregulated in the medial thalamus; TET3 mRNA levels were reduced in the medial prefrontal cortex and caudate-putamen; DNMT1 was downregulated in the caudate-putamen and medial thalamus. No statistically significant changes in expression were observed with DNMT3a. Our results suggest a complex functional role of these genes in different brain areas in the context of neuropathic pain. The notion of DNA methylation and hydroxymethylation being cell type-specific and not tissue-specific, and the possibility of chronologically differential gene expression after the establishment of neuropathic or inflammatory pain models ought to be addressed in future studies.